René Magritte : selected writings - Magritte, René (University of Minnesota Press, 2016)
Cover; Half Title; Title; Copyright; Contents; Key to the Abbreviations in the Annotations; Editors' Note on French Titles; The Double Agent: A Preface; The Alphabet of Revelations: An Introduction; Selected Writings; Pure Art: A Defence of the Aesthetic; Norine Blues; Texts from 391; Texts from Période; Texts from Œsophage; Texts from Marie; You; The Legs of the Sky; Nick Carter; Personal Experience; The Man with the Aimless Face; "He Had Set out Alone & ; Notes on Fantômas; "All Precautions & ; "Her Heart Is Mine & ; The Colours of the Night; "Communal Action &